Xeno-free approach for the expansion of human adipose derived mesenchymal stem cells for ocular therapies. (January 2021) - Persinal-Medina, M.; Llames, S.; Vázquez, N.; Chacón, M.; Acebes-Huerta, A.; Uribe, E.; Alonso-Alonso, S.; Fernández-Vega González, C.; Baamonde, B.; Quirós, L.; Merayo-Lloves, J.; Meana, Á.
Abstract: To restore corneal transparency and vision loss after an injury on the ocular surface, the use of human stem cells from different origins has been recently proposed. Mesenchymal stem cells (MSCs) seem to be an appropriate adult source of autologous stem cells due to their accessibility, high proliferation rate, and multipotent capacity. In this work, we developed a simple culture system to prepare a graft based on a fibrin membrane seeded with human MSCs. A commercial kit, PRGF Endoret®, was used to prepare both, the growth factors used as culture media supplement and the fibrin membrane grafts. Adipose-derived MSCs (Ad-MSCs) were expanded, characterised by flow cytometry and their multilineage differentiation potential confirmed by inducing adipogenesis, osteogenesis and chondrogenesis. Ad-MSCs seeded on the fibrin membranes were grafted onto athymic mice showing good biocompatibility with no adverse reactions observed during the follow up period. These findings support the assumption that a system in which all the biological components (cells, grow factors and carrier) are autologous, could potentially be used for future ex vivo expansion of Ad-MSCs to treat ocular conditions such as an inflammatory milieu, traumatic scars and loss of the regenerative capacity of the corneal epithelium that compromise the quality of vision. Highlights: The extraction of adipose tissue is minimally invasive. Human growth factors derived from blood plasma can be used to in vitro expand human MSCs. Autologous fibrin membranes can replace allogenic amniotic membranes for in vivo transplantation of MSCs. PRGF fibrin membrane combined with Ad-MSCs does not produce postsurgical inflammation in vivo.